An insight into neonatal unconjugated hyperbilirubinaemia from the transfusion medicine perspective. (10th May 2020) - Routray, Suman Sudha; Ray, Gopal Krushna; Prakash, Satya; Mishra, Debasish; Das, Pankaj Kumar; Mukherjee, Somnath
Abstract : Unconjugated hyperbilirubinaemia is a common cause of morbidity and mortality among neonates in Asian and African countries. The aetiology is multifactorial and has wide range of presentation ranging from simple physiological jaundice to severe HDN requiring prompt intervention to prevent long‐term neurological sequelae. Extensive detection of borderline raised bilirubin level in newborn is debatable as it may lead to inappropriately increased phototherapy and unnecessary increased hospital stay. However, those at risk like early presentation of hyperbilirubinaemia within 48 h, prolonged hyperbilirubinaemia, and family history in siblings or having history of HDN must be screened for immune as well as non‐immune causes to prevent the neonate from further severe form of complications. Along with direct antiglobulin test, elution, antibody screening/identification is performed to evaluate the immune causes. Improvement in the molecular technology leads to prompt diagnosis of non‐immune causes which were previously remained as idiopathic. This will aid in the early management like phototherapy or exchange transfusion as per the indication. This review will basically focus on the aetiopathogenesis of neonatal unconjugated hyperbilirubinaemia and approach to immune causes from transfusion medicine prospective.